TINGKAT PENGETAHUAN TENTANG ANTIBIOTIK PADA MAHASISWA - Aulia Rahmi, Ika (Journal of Pharmacy Tiara Bunda, 2025)
Antibiotics are widely prescribed drugs. The relatively high and inappropriate use of antibiotics can cause various problems consequently become a global threat to health, especially due to bacterial resistance. The purpose of this study was to determine the level of students’ knowledge on the use of antibiotics and correlate between the level of knowledge of antibiotics with the frequency of using antibiotics without a prescription for students at the Politeknik Tiara Bunda. The study used a descriptive method with cross-sectional design. It was conducted from May to June, 2021 Respondents were 250 students from Politeknik Tiara Bunda., selected by using proportional sampling technique. The results of this study showed that 52.4% of the students at Politeknik Tiara Bunda. had moderate, 27.2% good and 20.4% less of knowledge about antibiotics, while the frequency of use of antibiotics without prescription at 44.8%. Chi-square test results showed that the students’ level of knowledge was affected by origin of faculty (p < 0.05), whereas gender, age and origin of place does not significantly affect the students’ level of knowledge (p > 0.05). The correlate between the pharmacy with non-pharmacy students’ knowledge was at (p < 0.05), as well as the correlate between students’ knowledge with the frequency of use of antibiotics without prescription, thus proving that there was a significant correlation between pharmacy with non-pharmacy students’ knowledge and between students’ level of knowledge with the frequency of use of antibiotics without prescription